2017
DOI: 10.1038/srep44779
|View full text |Cite
|
Sign up to set email alerts
|

Identification of cancer-associated missense mutations in hace1 that impair cell growth control and Rac1 ubiquitylation

Abstract: The E3 ubiquitin ligase HACE1 is a potent tumor suppressor that controls cell proliferation and ubiquitylates the small GTPase Rac1 to target it to proteasomal degradation. Whether and how the activity of HACE1 is regulated by the N-terminal ankyrin (ANK) and the middle (MID) domains is ill defined. Here, we identified in the version 64 of the Catalogue of Somatic Mutations in Cancer (COSMIC) 13 missense mutations of hace1 located outside the HECT domain, and found that all lead to defective control of cell pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
24
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 26 publications
3
24
0
Order By: Relevance
“…Moreover, HACE1 down-regulation cooperates with ErbB2/HER2 overexpression in mammary cells to induce Rac1 hyperactivation, migration, malignant transformation, and tumorigenesis in vivo , effects that are sensitive to pharmacological Rac inhibition (27). A very recent report that identified cancer-associated missense mutations in HACE1 leading to defective Rac1 ubiquitination highlights the relevance of the control of Rac1 expression in cancer cell proliferation (28). …”
Section: Emerging Paradigms In Rho Gtpase Hyperactivation In Cancermentioning
confidence: 99%
“…Moreover, HACE1 down-regulation cooperates with ErbB2/HER2 overexpression in mammary cells to induce Rac1 hyperactivation, migration, malignant transformation, and tumorigenesis in vivo , effects that are sensitive to pharmacological Rac inhibition (27). A very recent report that identified cancer-associated missense mutations in HACE1 leading to defective Rac1 ubiquitination highlights the relevance of the control of Rac1 expression in cancer cell proliferation (28). …”
Section: Emerging Paradigms In Rho Gtpase Hyperactivation In Cancermentioning
confidence: 99%
“…HECT domain and ankyrin repeat‐containing E3 ubiquitin protein Ligase (HACE1), one member of the HECT domain‐containing E3 ligase family, was first brought into our attention by the study of Wilms’ tumor and was then frequently found lost or down‐regulated in many kinds of tumors , suggesting its role as a tumor suppressor. However, its special and pivotal role in tumor suppression was merely understood except for some discoveries suggesting that HACE1 could restrain reactive oxygen species generation , control cell fate through regulating TNFR1 , and impede cell growth by accelerating ubiquitylation of Rac1 . In previous work, we uncovered a special function of HACE1 as suppressing tumors by enhancing selective autophagy .…”
Section: Introductionmentioning
confidence: 99%
“…proteins [57,58,[61][62][63][64][65]. Expanded studies on how HACE1 binds and recognizes its substrates are needed to further clarify the role of HACE1 in cancer development.…”
Section: Hace1 a Prominent Tumor Suppressor With Dual Functionmentioning
confidence: 99%